Upper-flow regime bedforms in a subglacial triangular-shaped landform (murtoo), Late Pleistocene, SW Finland: Implications for flow dynamics and sediment transport in (semi-)distributed subglacial meltwater drainage systems - Hovikoski, J.; Mäkinen, J.; Winsemann, J.; Soini, S.; Kajuutti, K.; Hepburn, A.; Ojala, A.E.K. (Amsterdam [u.a.] : Elsevier, 2023)
We know less about subglacial meltwater flow properties in distributed inefficient and semi-efficient systems in comparison to those of ice marginal eskers and proglacial environments. While previous studies have indicated the overall common presence of upper-flow-regime (UFR) bedforms in glacigenic settings, facies expressions of subglacial meltwater flows remain poorly documented. Three ca. 3 m deep and up to 70 m long trenches excavated across a triangle-shaped subglacial landform called a murtoo in a Lateglacial to Holocene meltwater route in SW Finland provide a detailed window into sedimentary structures presumably formed ca. 40–50 km away from the coeval subaqueous margin of the Fennoscandian Ice Sheet (FIS). The aim of this paper is to document small-scale bedforms, which formed subglacially by meltwater flow and to characterize the proximal and central parts of the studied murtoo during its early evolutionary phase. We defined seven main facies types that characterize the depositional processes of the unit. Overall, the studied deposits reflect increasing meltwater delivery through time and are characterized by abrupt lateral changes in sedimentary structures and grain size. While the initial deposits are dominated by massive and horizontally laminated silt with sand lenses interpreted as lower-flow-regime deposits, the latter sediments are characterized by sinusoidal stratification, sigmoidal cross-stratification and scours with backsets or chaotic fill interpreted as deposits of antidunes, humpback dunes, chutes-and-pools and cyclic steps of the upper-flow regime. The upper-flow-regime bedforms developed on a 1 m high and 15 m long bed slope and are associated with the formation of a short-lived enlarged water-filled cavity or pond, where supercritical density flows allowed for the deposition of upper-flow regime bedforms. The final coarse-grained murtoo head-bar development, characterized by planar-cross stratified gravel and pebbly sand, indicates avalanche processes that were controlled by grain ...